Cloning, expression and characterisation of a novel mollusc α-1,2-Fucosyltransferase from Crassostrea gigas (CgFUT2) - Zemkollari, Marilica; Ruprecht, Colin; Blaukopf, Markus; Grabherr, Reingard; Staudacher, Erika (Glycoconjugate journal, 2024)
Glycans containing fucose play crucial roles in cell biology, particularly in recognition processes. In humans, fucose found in H-blood group antigens is recognized by various pathogens, thereby influencing host-pathogen interactions. However, in invertebrate biology the specific functions of these modifications and the corresponding glycosyltransferases are not fully elucidated. Therefore, cloning these glycosyltransferases from different model systems will provide valuable insights into this process. Little is known about fucosyltransferases in molluscs. For this study, a sequence of the Pacific oyster, Crassostrea gigas , based on amino acid sequence homologies with rabbit and human α-1,2-fucosyltransferases, was chosen. The recombinant enzyme (350 amino acids) was able to transfer fucose from GDP-fucose to the galactose residue of type II disaccharides, terminal galactoses in complex N-glycan structures and several linear and branched galactans which were tested using a glycan microarray. The α-1,2-linkage formed was confirmed by NMR analysis. The enzyme was active in a broad pH-range, it was relatively stable upon storage conditions and its activity was not dependent on the presence of divalent cations. In this study, we were able to clone, express and characterise a novel α-1,2-fucosyltrasferase from Crassostrea gigas ( Cg FUT2).